2022
DOI: 10.21873/anticanres.15793
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Early Death Within Three Months from the Start of Immune Checkpoint Inhibitors in Patients With Different Types of Cancer

Abstract: Background/Aim: Implementation of new anti-cancer treatments in rural healthcare might not always result in identical survival outcomes as those seen in the randomized trials leading to approval. Therefore, the survival of patients treated with immune checkpoint inhibitors (ICI) in Nordland county was analyzed. Materials and Methods:Retrospective analysis of 199 patients, mainly treated in adjuvant or palliative settings, e.g. for non-small cell lung cancer (NSCLC) or malignant melanoma (2018)(2019)(2020)(2021… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In our hospital's ICI-treated cancer patient population, a previous retrospective study focusing on those with short survival (maximum 3 months from start) has shown that presence of brain metastases was not among the factors explaining such unfavorable outcome, in contrast to reduced performance status (PS) or advanced age [15]. Given that patients with brain metastases represent a particular, potentially vulnerable subgroup (especially if suffering from reduced neurological or cognitive function), a detailed analysis of patterns of care and survival in an expanded database appeared warranted.…”
Section: Introductionmentioning
confidence: 93%
“…In our hospital's ICI-treated cancer patient population, a previous retrospective study focusing on those with short survival (maximum 3 months from start) has shown that presence of brain metastases was not among the factors explaining such unfavorable outcome, in contrast to reduced performance status (PS) or advanced age [15]. Given that patients with brain metastases represent a particular, potentially vulnerable subgroup (especially if suffering from reduced neurological or cognitive function), a detailed analysis of patterns of care and survival in an expanded database appeared warranted.…”
Section: Introductionmentioning
confidence: 93%
“…Immune checkpoint inhibitors (ICIs) have transformed treatment for many advanced carcinomas including non-small cell lung cancer (NSCLC) (1)(2)(3)(4). The long-tailed plateau of survival curves in patients receiving ICI therapy is extremely positive, with a considerable cure rate in patients with advanced NSCLC (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…Immune checkpoint inhibitors (ICIs) have transformed treatment for many advanced carcinomas including non-small cell lung cancer (NSCLC) (1)(2)(3)(4). The long-tailed plateau of survival curves in patients receiving ICI therapy is extremely positive, with a considerable cure rate in patients with advanced NSCLC (1)(2)(3)(4). With conventional cytotoxic antitumour drugs, dosing and treatment intervals are determined by pharmacokinetics and pharmacodynamics, such as drug half-life and blood concentrations (5).…”
mentioning
confidence: 99%